Actividad antagonista de PGPR en nematodos fitoparásitos Pratylenchus spp. y Radopholus similis en Musa acuminata (cavendish). - Crespo Avila, Jorge Abel (2019)
The constant application of nematicides in the banana crop to the control of Pratylenchus spp. and R. similis, has led to a considerable reduction of beneficial soil microorganisms, generating the proliferation of pathogens and environmental contamination. The use of biological controllers such as rhizobacteria that promote plant development (PGPR) in agriculture is an alternative that benefits the physiological aspects of plants and in turn the reduction of nematicides. This research work was carried out in the Microbiology and Molecular Biology laboratories of the State Technical University of Quevedo (UTEQ). The objective of this work was to evaluate the antagonistic activity of PGPR in Pratylenchus spp. and Radopholus similis in Musa acuminata. The morphological and molecular characterization by PCR was performed by the pair of first D3A (5-GACCCGTCTTGAAACACGGA-3) and D3B (5-TCGGAAGGAACCAGCTACTA-3) with Pratylenchus spp. Massive reproduction platforms were designed for the nematodes using carrot discs and Musa paradisiaca seedlings, obtaining averages of 13,212 and 11,156 nematodes, respectively. The evaluation of the in vitro antagonistic assays used the strains: A. calcoaceticus (PM2-12), S. marcescens (PM3-8), P. veronii (R4) and K. variicola (BO 3-4). in vitro antagonistic activity in stage J2 nematode: obtaining greater antagonism with strains M2-12, R4 with an average higher than 90 and 82% respectively. The ex vivo assays were used bacterial combinations (R4, PM2-12, PM3-8); the variables evaluated; were root weight with 164.73g, higher than the plants without inoculant with 66.13g; with the bacterial combination, 29 roots were obtained superior to the control with 19 roots; the percentage of functional roots was 70% compared to the control that was obtained 54%; the length of the pseudostem was 37.87cm higher than the control with an average of 28.6cm; the highest chlorophyll content was 13.42 mg / cm2 higher than the control with 9.48 mg / cm2. The lowest population of J2 was obtained with the bacterial combination with 2,100 while the control with 5,100 nematodes. This confirms the effectiveness of PGPR as a biological alternative for the control of phytonematodes providing greater protection to crops. Keywords: PGPR, Pratylenchus, Radopholus similis medio M3, PCR